Pengembangan Aktivitas Pengajian Anak oleh Ibu Rumah Tangga: Penelitian Tindakan di Balai Pengajian Firya Lientas Lhokseumawe - Astuti, Dewi; Isnaniar, Isnaniar; Chairunnisa, Chairunnisa; Salabi, Agus Salim; Munadi, Munadi; Samhudi, Samhudi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IAIN Lhokseumawe, 2024)
This study aims to explore and develop a learning program for children’s religious education at the Firya Lientas Housing Community in Lhokseumawe. The research employs an action research approach with qualitative methods to understand and enhance the effectiveness of the program. The methodology involves five main steps: problem identification, action planning, action implementation, observation and data collection, and reflection. Data were collected through participatory observation, in-depth interviews, and documentation. Data analysis was conducted using qualitative techniques, including transcription, coding, thematic development, and data interpretation. The results indicate that the development of religious education activities has had a positive impact, as evidenced by increased understanding of religious values and the development of social-emotional skills. The increased support from parents, demonstrated by their willingness to contribute financially to the program and the establishment of active communication for mutual support, also reflects the positive impact of these activities. The active involvement of housewives who serve as religious teachers (ustazah) in imparting religious values, developing social-emotional skills, providing moral support, and planning the children’s religious education activities has helped enhance understanding of religious values and social-emotional skills through the development of teaching materials, implementation of interactive learning strategies, and ongoing evaluation. Based on these findings, additional training and preparation are needed for housewives who serve as teachers (ustazah) to better equip them to competently support children’s education.